Peran Fisioterapi Komunitas dalam Peningkatan Kesadaran Dini Stroke pada Keluarga dan Komunitas di Puskesmas Kendalsari - Ahmad Putri, Cici Farida; Rahmanto, Safun; Suharto, Bonita (Rena Cipta Mandiri, 2025)
Introduction: Stroke is a serious medical condition caused by a disruption of blood flow to the brain, leading to brain tissue damage, permanent disability, or even death. Increasing early awareness and understanding of stroke among families and communities is essential to promote early detection, risk factor prevention, and timely management. Objective: This community service aimed to educate families and communities about the definition of stroke, risk factors, warning signs, and preventive measures to reduce stroke incidence and its impacts. Methods: The method used was direct health education to the community, utilizing leaflets as educational media, combined with interactive lectures and question-and-answer sessions. Pre-tests and post-tests were conducted to assess participants' understanding before and after the education session. Conclusion: The health education session was conducted successfully. There was a noticeable increase in participants' understanding, as evidenced by improved post-test results. This activity is expected to encourage families and communities to be more alert to stroke and to implement preventive measures early.